Kontrol Keluarga dan Kemungkinan untuk Membayar Dividen: Pengaruh Volatilitas Arus Kas - Kusumawati, Nunik Dwi (Journal of Business & Banking, 2022)
This study aims to analyze the effect of family control on the likelihood of paying dividends with cash flow uncertainty as a moderating variable in manufacturing companies listed on the Indonesia Stock Exchange. This study analyzed the data by using Logistic Regression and the sample by a purposive sampling in the sampling method. The results show that family firms have a lower probability of paying dividends than non-family firms. However, cash flow uncertainty only acts as a predictor variable and does not moderate the effect of family control on the likelihood of paying dividends. The implication is that family companies have a lower probability of paying dividends compared to non-family companies, so investors need to consider the type of company in selecting investments in the company.